2016
DOI: 10.1002/jmri.25292
|View full text |Cite
|
Sign up to set email alerts
|

Can diffusion tensor anisotropy indices assist in breast cancer detection?

Abstract: Water diffusion anisotropy in the healthy breast can be similarly mapped by the normalized indices and by λ -λ . However, the normalized anisotropy indices fail to differentiate cancer from normal breast tissue, whereas λ -λ can assist in differentiating cancer from normal breast tissue. J. Magn. Reson. Imaging 2016;44:1624-1632.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
1
35
1
Order By: Relevance
“…Malignant transformation may in turn cause blockage of the ducts by proliferating neoplastic cells and loss of structured organization, resulting in a concomitant reduction of anisotropy measures, Figure . Indeed, two studies demonstrated FA to be significantly reduced in malignancies versus normal breast tissue, although several other DTI studies found no difference …”
Section: Emerging Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…Malignant transformation may in turn cause blockage of the ducts by proliferating neoplastic cells and loss of structured organization, resulting in a concomitant reduction of anisotropy measures, Figure . Indeed, two studies demonstrated FA to be significantly reduced in malignancies versus normal breast tissue, although several other DTI studies found no difference …”
Section: Emerging Techniquesmentioning
confidence: 99%
“…Typical DWI acquisitions have Δ in the range of 35–50 ms, corresponding to an approximate (one dimensional) diffusion displacement l=2DΔ of 14–17 μm for unrestricted free water at body temperature (D∼3 × 10 ‐3 mm 2 /s). Diffusion time was found to affect anisotropy measures of normal fibroglandular tissue, with reduced anisotropy values observed for all indices following shortening of the diffusion time from 47 to 33 ms …”
Section: Emerging Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the source of anisotropy is uncertain: a preclinical breast cancer model observed lower FA in hypoxic regions with lower collagen fibre content, but the differences between normoxic and hypoxic FAs were small, approximately 0.03. Other groups have suggested partial restriction in the breast ducts, although the average duct diameter (approximately 90 μm in normal breast and larger in patients with ductal carcinoma in situ ) is much larger than the average distance travelled by water molecules during typical diffusion MRI experiments.…”
Section: Introductionmentioning
confidence: 92%